Probing behaviour of Cacopsylla pyri on a resistant pear selection. (31st August 2012) - Civolani, S.; Grandi, G.; Chicca, M.; Pasqualini, E.; Fano, E. A.; Musacchi, S.
Abstract European pear psylla Cacopsylla pyri L. (Hemiptera Psyllidae) is one of the worst pests of pear (Pyrus communis L.) in Europe. We investigated probing behaviour in adults and nymphs of C. pyri by full EPG on a psylla‐resistant pear selection, NY 10353. Concerning stylet probing behaviour on the plant surface, the results showed no significant differences between the resistant selection and the susceptible cultivar Bartlett, and no differences were also detected for epidermis and mesophyll resistance in the same conditions. For mesophyll/phloem, no differences were found in adults. However, in nymphs, weak resistance factors (longer stylet penetration and mesophyll salivation) were detected in the resistant selection. In phloem, EPG data indicate strong resistance factors in NY 10353, especially for nymphs and summer‐form adults (longer time before the first phloem ingestion and a lower duration of each phloem ingestion event). No prolonged (>10 min) phloem ingestion was performed by nymphs and adults in the resistant selection. The results support the hypothesis that NY 10353 resistance factors are located in the phloem sap and cause high C. pyri nymph mortality: this could be useful as a basis for further investigations of resistance mechanisms at the metabolic, chemical and genetic levels.